Structural Analysis of Treatment Cycles Representing Transitions between Nursing Organizational Units Inferred from Diabetes. - Matthias Dehmer; Zeyneb Kurt; Frank Emmert-Streib; Christa Them; Eva Schulc; Sabine Hofer (PLoS ONE, 2015)
In this paper, we investigate treatment cycles inferred from diabetes data by means of graph theory. We define the term treatment cycles graph-theoretically and perform a descriptive as well as quantitative analysis thereof. Also, we interpret our findings in terms of nursing and clinical management.